Preparation method and application of gel polymer electrolyte containing dynamic side chain
By using gel polymer electrolytes containing dynamic side chains in lithium sulfur batteries, the problem of slow kinetics of polysulfide shuttle and electrochemical reactions in the battery is solved, and high-capacity and long cycles of high-performance lithium sulfur batteries are achieved.
Patent Information
- Application Number
- CN202411937809.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In existing lithium-sulfur batteries, gel polymer electrolytes have problems such as polysulfide shuttle, slow electrochemical reaction kinetics and poor circulation performance.
Gel polymer electrolytes containing dynamic side chains are used, which regulate the solvated structure of lithium ions and the interaction between the electrolyte/electrode interface by introducing dynamic covalent bonds and strong polar groups on the polymer backbone, and promote lithium salt dissociation and electrochemical reaction kinetics.
The capacity and circulation stability of lithium-sulfur batteries have been significantly improved, especially in low temperature environments, and the utilization rate of active substances and the overall performance of the battery are improved.
Smart Images

Figure CN119742440A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of gel polymer electrolytes, and in particular relates to a preparation method of a gel polymer electrolyte containing dynamic side chains and application thereof. Background Art
[0002] At present, lithium-sulfur batteries generally use liquid electrolytes mixed with volatile and flammable ether-based organic solvents and lithium salts, which have safety hazards such as easy leakage, flammability and explosion. Lithium-sulfur batteries are considered to be one of the most promising new secondary energy storage systems due to their high theoretical specific capacity (1675mAh / g) and high theoretical energy density (2600Wh / kg). High energy density and long-life lithium-sulfur batteries can meet the urgent needs of military and civilian dual-use. However, the "shuttle effect" of soluble polysulfides formed during the discharge of lithium-sulfur batteries in liquid electrolytes, slow polysulfide conversion kinetics, and the growth of lithium dendrites at the negative electrode have seriously affected the actual performance of lithium-sulfur batteries. Polymer all-solid electrolytes can fundamentally avoid the safety issues of electrolyte leakage, polysulfide shuttling and lithium dendrite growth. However, the poor contact between the all-solid electrolyte and the electrode interface leads to high interface impedance and slow reaction kinetics, which hinders the development of all-solid-state lithium-sulfur batteries. Gel polymer electrolytes have good compatibility with electrode interfaces because they contain more liquid electrolyte components. They have better mechanical properties than liquid electrolytes and better ionic conductivity than all-solid-state electrolytes. They can inhibit the growth of lithium dendrites to a certain extent and improve battery safety.
[0003] Gel polymer electrolytes are expected to solve the various challenges faced by lithium-sulfur batteries and have great application potential. However, due to the presence of liquid electrolytes, the "shuttle effect" and lithium dendrite growth are still unavoidable, and the electrochemical reaction kinetics are slow, which seriously affects the performance of lithium-sulfur batteries.
[0004] Gel polymer electrolytes are generally obtained by swelling a polymer matrix in lithium salts and liquid plasticizers by physical and chemical methods (such as patent CN202110428183.7). The contact between the electrolyte and the electrode prepared by this method is not close, and the polymer skeleton is difficult to penetrate into the electrode pores. In situ polymerization gel polymer electrolytes solve this problem very well. The polymer electrolyte generated in situ not only has good stability and low interfacial impedance, but also has a high solution absorption rate, and can more uniformly fix the liquid electrolyte in the cross-linked network. In the prior art, the polymer skeleton in the gel polymer electrolyte is easy to modify, and modifying a variety of polar groups (such as ester groups, amino groups, sulfonic acid groups, etc.) on the polymer skeleton helps to increase the dissociation rate of lithium salts and accelerate lithium ion transmission. However, the introduction of strong polar groups will increase the adsorption energy of lithium ions and polymers, making it difficult for lithium ions to escape from the strong polar solvation structure to participate in the polysulfide conversion reaction, thereby resulting in slow reaction kinetics and reducing the utilization rate of active substances. Therefore, it is urgent to solve the problems of low active utilization rate, slow electrode reaction kinetics and poor cycle stability of lithium-sulfur batteries. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of polysulfide shuttling, slow electrochemical reaction kinetics and poor cycle performance in existing lithium-sulfur battery gel polymer electrolytes, and to provide a gel polymer electrolyte and a preparation method thereof and application in a low temperature environment.
[0006] In order to achieve the above objectives, the present invention provides the following technical solutions.
[0007] A method for preparing a gel polymer electrolyte containing dynamic side chains comprises the following steps:
[0008] Step S1. Preparation of monomers containing dynamic covalent bonds.
[0009] The monomer containing phenylboronic acid is dissolved in an alcohol solvent, stirred at 20-40°C for 1-2 hours to obtain solution A; 3-amino-1,2-propanediol is dissolved in an alcohol solvent, stirred at 20-40°C for 1-2 hours to obtain solution B; solution A and solution B are mixed in a volume ratio of 1:1, anhydrous magnesium sulfate (MgSO4) is added, stirred at 20-40°C for 12-24 hours, the upper suspension is taken, and rotary evaporated at 60-80°C for 4-6 hours to obtain a concentrated solution; ether is added to the concentrated solution to precipitate a light yellow solid, and the light yellow solid is vacuum dried at 60-80°C for 12-24 hours to obtain a monomer containing a dynamic covalent bond.
[0010] Furthermore, in step S1, the alcohol solvent is one or a mixture of two or more of methanol, ethanol and propanol.
[0011] Among them, the molar ratio of phenylboronic acid monomer to alcohol solvent is 1:(20-40); the molar ratio of 3-amino-1,2-propanediol to alcohol solvent is 1:(20-40); the molar ratio of anhydrous magnesium sulfate to phenylboronic acid monomer is (1-2):1; and the molar ratio of ether to phenylboronic acid monomer is (20-30):1.
[0012] Step S2. Add the monomer containing dynamic covalent bonds, the cross-linking agent having two or more functional groups, the monofunctional allyl linear monomer and the initiator obtained in step S1 into the electrolyte of the lithium-sulfur battery, and stir evenly to obtain a gel polymer electrolyte precursor;
[0013] Step S3: The gel polymer precursor is thermally initiated to polymerize in situ to obtain a gel polymer electrolyte containing dynamic side chains.
[0014] Furthermore, in step S1, the phenylboronic acid-containing monomer is one or a mixture of two or more of 3-cyanophenylboric acid, 2-fluorophenylboric acid, 2,3,6-trifluorophenylboric acid, and 3,4,5,6-tetrafluorophenylboric acid.
[0015] Furthermore, in step S2, the monomer containing dynamic covalent bonds obtained in step S1 accounts for 1-5% of the total mass of the gel polymer precursor.
[0016] Furthermore, in step S2, the difunctional or higher cross-linking agent is one or a mixture of two or more of the following: polydipentaerythritol hexaacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, polyethylene glycol dimethacrylate (molecular weight of 200-400 g / mol); the difunctional or higher cross-linking agent accounts for 1-5% of the total mass of the gel polymer precursor.
[0017] Furthermore, in step S2, the monofunctional allyl linear monomer is one or a mixture of two or more of 2-((allyloxy)methyl)ethylene oxide, 2-((2-(vinyloxy)ethoxy)methyl)ethylene oxide, and 2-(ethylene oxide)methacrylate; and the monofunctional allyl linear monomer accounts for 1-5% of the total mass of the gel polymer precursor.
[0018] Furthermore, in step S2, the initiator is one or a mixture of two or more of azobisisoheptanonitrile, azobisisobutyronitrile, dibenzoyl peroxide, and methyl ethyl ketone peroxide, and the initiator accounts for 1-5% of the total mass of the gel polymer precursor.
[0019] Further, in step S2, the electrolyte of the lithium-sulfur battery is specifically: dissolving lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) and LiNO3 in 1,3-dioxolane (DOL) and 1,2-ethylene glycol dimethyl ether to obtain the electrolyte of the lithium-sulfur battery. Among them, the volume ratio of 1,3-dioxolane (DOL) and 1,2-ethylene glycol dimethyl ether is 1:1, the concentration of lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) is 1M, and LiNO3 accounts for 2wt% of the total mass of the electrolyte.
[0020] Furthermore, in step S3, the thermal initiation temperature is 50-80° C., and the polymerization time is 1-4 h.
[0021] The gel polymer electrolyte containing dynamic side chains prepared by the above method can be applied to lithium-sulfur batteries.
[0022] Beneficial effects of the present invention:
[0023] The polar groups (such as carbonyl and ether oxygen) in the gel polymer electrolyte containing dynamic side chains of the present invention can promote the dissociation of lithium salts as electron donors to form Li + Fast migration channel. Strong polar groups in dynamic side chains (such as cyano and fluorine) can regulate the interaction between functional groups in polymers and nearby Li + The ion-dipole interaction of recombinant Li + Solvation structure, improving Li + At the same time, the movement of dynamic bonds on the polymer matrix can accelerate the Li + Desolventization accelerates the conversion kinetics of polysulfides and significantly improves the capacity and cycle stability of lithium-sulfur batteries in an environment of 0-25°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Graphs showing the ionic conductivity of Example 1, Comparative Example 1 and Comparative Example 2.
[0025] Figure 2 The electrochemical window diagrams of Example 1, Comparative Example 1 and Comparative Example 2 are shown.
[0026] Figure 3 Graph showing the coulombic efficiency of Li-Cu half-cells of Example 1, Comparative Example 1 and Comparative Example 2.
[0027] Figure 4 The 0.1C charge and discharge curves of Example 2, Comparative Example 1 and Comparative Example 2 are shown.
[0028] Figure 5 It is the rate performance diagram of Example 2, Comparative Example 1 and Comparative Example 2.
[0029] Figure 60.5C long cycle performance diagram of Example 3, Comparative Example 1 and Comparative Example 2.
[0030] Figure 7 It is a long cycle performance diagram of Example 1, Comparative Example 1 and Comparative Example 2 at 0°C and 0.5C. DETAILED DESCRIPTION
[0031] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0032] Example 1
[0033] S1: Weigh 14.7g of 3-cyanophenylboronic acid and dissolve it in 93ml of methanol, stir at 20℃ for 1h to obtain solution A; weigh 9.1g of 3-amino-1,2-propanediol and dissolve it in 65ml of methanol, stir at 20℃ for 1h to obtain solution B; mix solution A and solution B, add 19g of anhydrous magnesium sulfate (MgSO4), and stir at 20℃ for 12h; take the upper suspension, rotary evaporate at 60℃ for 4h to obtain a concentrated solution; add 220ml of ether to the concentrated solution to precipitate a light yellow solid, and dry the light yellow solid in vacuo at 60℃ for 12h to obtain the final product C.
[0034] S2: Weigh 0.01 g of polydipentaerythritol hexaacrylate, 0.05 g of 2-((allyloxy)methyl)ethylene oxide, 0.05 g of product C and 0.025 g of azobisisobutyronitrile, add them to 0.865 g of electrolyte and mix them evenly to obtain a gel polymer electrolyte precursor.
[0035] S3: The gel polymer precursor is thermally initiated to be in situ polymerized at 50° C. for 4 h to obtain a gel polymer electrolyte containing dynamic side chains.
[0036] Example 2
[0037] S1: Weigh 14.1g of 2-fluorophenylboronic acid and dissolve it in 100ml of ethanol, stir at 30℃ for 1.5h to obtain solution A; weigh 9.1g of 3-amino-1,2-propanediol and dissolve it in 100ml of ethanol, stir at 30℃ for 1.5h to obtain solution B; mix solution A and solution B, add 27g of anhydrous magnesium sulfate (MgSO4), and stir at 30℃ for 18h; take the upper suspension, rotary evaporate at 70℃ for 5h to obtain a concentrated solution; add 190ml of ether to the concentrated solution to precipitate a light yellow solid, and dry the light yellow solid in vacuo at 70℃ for 18h to obtain the final product C.
[0038] S2: Weigh 0.05 g of pentaerythritol tetraacrylate, 0.025 g of 2-(ethylene oxide) methacrylate, 0.025 g of product C and 0.01 g of dibenzoyl peroxide, add them to 0.89 g of electrolyte and mix them evenly to obtain a gel polymer electrolyte precursor.
[0039] S3: The gel polymer precursor is thermally initiated to be in situ polymerized at 80° C. for 1 h to obtain a gel polymer electrolyte containing dynamic side chains.
[0040] Example 3
[0041] S1: Weigh 17.6g of 2,3,6-trifluorophenylboric acid and dissolve it in 150ml of propanol, stir at 40°C for 2h to obtain solution A; weigh 9.1g of 3-amino-1,2-propanediol and dissolve it in 130ml of propanol, stir at 40°C for 2h to obtain solution B; mix solution A and solution B, add 45g of anhydrous magnesium sulfate (MgSO4), and stir at 40°C for 24h; take the upper suspension, rotary evaporate at 80°C for 6h to obtain a concentrated solution; add 240ml of ether to the concentrated solution to precipitate a light yellow solid, and vacuum dry the light yellow solid at 80°C for 24h to obtain the final product C.
[0042] S2: Weigh 0.025 g of polyethylene glycol dimethacrylate (molecular weight 200 g / mol), 0.05 g of 2-((2-(vinyloxy)ethoxy)methyl)ethylene oxide, 0.05 g of product C and 0.05 g of methyl ethyl ketone peroxide, add them to 0.825 g of electrolyte and mix well to obtain a gel polymer electrolyte precursor.
[0043] S3: The gel polymer precursor is thermally initiated to be in situ polymerized at 65° C. for 2.5 h to obtain a gel polymer electrolyte containing dynamic side chains.
[0044] Comparative Example 1
[0045] S1: Weigh 0.01 g of polydipentaerythritol hexaacrylate, 0.05 g of 2-((allyloxy)methyl)ethylene oxide and 0.025 g of azobisisobutyronitrile, add them to 0.915 g of electrolyte and mix them evenly to obtain a gel polymer electrolyte precursor.
[0046] S3: The gel polymer precursor is thermally initiated to be in situ polymerized at 50° C. for 4 h to obtain a gel polymer electrolyte containing dynamic side chains.
[0047] Comparative Example 2
[0048] Comparative Example 2 is an electrolyte for a lithium-sulfur battery without any monomers. Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and a certain amount of LiNO3 are dissolved in 1,3-dioxolane (DOL) and 1,2-ethylene glycol dimethyl ether to obtain an electrolyte for a lithium-sulfur battery. The volume ratio of 1,3-dioxolane (DOL) and 1,2-ethylene glycol dimethyl ether is 1:1, the concentration of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is 1M, and LiNO3 accounts for 2wt% of the total mass of the electrolyte.
[0049] Application Examples
[0050] The gel polymer electrolyte and lithium-sulfur battery electrolyte prepared in the embodiment and comparative example were used as the test electrolyte, and the carbon / sulfur powder positive electrode material was prepared by a simple melt diffusion method. The carbon / sulfur powder positive electrode material, the conductive agent Super P, and the binder PVDF-900 were mixed at a mass ratio of 7:2:1, and a certain amount of N-methylpyrrolidone was added and mixed evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on a carbon-coated aluminum foil, and the positive electrode sheet was obtained after drying, rolling, and slitting. The lithium sheet was used as the negative electrode, and the CR2032 button battery was assembled in a glove box filled with argon. The following is the material characterization and performance test of the selected specific examples.
[0051] Figure 1 Graphs showing the ionic conductivity at different temperatures of Example 1, Comparative Example 1 and Comparative Example 2. It can be found that Example 1 and Comparative Example 2 have the same order of magnitude of ionic conductivity.
[0052] Figure 2 The electrochemical window diagrams of Example 1, Comparative Example 1 and Comparative Example 2 are shown. The decomposition voltages of Example 1, Comparative Example 1 and Comparative Example 2 are 4.45 V, 4.13 V and 4.02 V, respectively, indicating that the electrochemical stability and anti-electrochemical oxidation ability of the gel polymer electrolyte containing dynamic side chains are improved.
[0053] Figure 3 The figure is the coulombic efficiency diagram of Li-Cu half-cell of Example 1, Comparative Example 1 and Comparative Example 2. It can be seen that the coulombic efficiency of Comparative Example 2 and Comparative Example 4 is greatly attenuated at 250 and 200 cycles, and the average coulombic efficiency of Example 1 is 98.2% after 600 cycles.
[0054] Figure 4 The 0.1C charge-discharge curves of Example 2, Comparative Example 1 and Comparative Example 2 are shown. It can be seen that at a current density of 0.1C, the capacity of Example 2 is 1445mAh / g, which is significantly higher than that of Comparative Example 1 and Comparative Example 2. The polarization voltages of Example 2, Comparative Example 1 and Comparative Example 2 are 138mV, 145mV and 166mV, respectively, indicating that the gel polymer electrolyte containing dynamic side chains accelerates the electrochemical reaction kinetics, reduces battery polarization, and improves the utilization rate of active materials.
[0055] Figure 5 The figure is a rate performance diagram of Example 2, Comparative Example 1 and Comparative Example 2. At current densities of 0.1C, 0.2C, 0.5C, 1C and 2C, the capacity of Example 2 is higher than that of Comparative Example 1 and Comparative Example 2, and at 2C, Example 2 can still provide a capacity of up to 840 mAh / g.
[0056] Figure 6The 0.5C long cycle performance diagram at 25°C for Example 3, Comparative Example 1 and Comparative Example 2. It can be seen that the initial discharge capacities of the lithium-sulfur batteries assembled in Example 3, Comparative Example 1 and Comparative Example 2 are 1088mAh / g, 842mAh / g and 947mAh / g, and the capacities of Example 3 and Comparative Example 1 after 1000 cycles are 583mAh / g and 360mAh / g, respectively, and the capacity of Comparative Example 2 after 400 cycles is 285mAh / g.
[0057] Figure 7 The 0.5C long cycle performance diagram of Example 1, Comparative Example 1 and Comparative Example 2 at 0°C. It can be seen that the initial discharge capacity of the lithium-sulfur batteries assembled in Example 1, Comparative Example 1 and Comparative Example 2 is 940mAh / g, 668mAh / g, 810mAh / g, and the capacity of Example 1, Comparative Example 1 and Comparative Example 2 after 200 cycles is 810mAh / g, 525mAh / g, 528mAh / g.
[0058] The gel polymer electrolyte containing dynamic side chains prepared by the present invention promotes the dissociation of lithium salts through a polymer skeleton rich in polar groups, thereby constructing a fast Li + The strong electronegative groups on the side chains mediate the Li transport channel through ion-dipole interactions. + The solvation structure and the movement of dynamic bonds on the polymer backbone accelerate the electrolyte / electrode interface treatment. + The desolvation accelerates the electrochemical reaction kinetics, improves the utilization rate of active materials, and ultimately realizes high-performance lithium-sulfur batteries with high capacity and long cycle.
Claims
1. A method for preparing a gel polymer electrolyte containing dynamic side chains, characterized in that: The following steps are involved: Step S1. Preparation of monomers containing dynamic covalent bonds; Dissolve the monomer containing phenylboronic acid in an alcohol solvent, stir at 20-40°C for 1-2 hours to obtain solution A; dissolve 3-amino-1,2-propanediol in an alcohol solvent, stir at 20-40°C for 1-2 hours to obtain solution B; mix solution A and solution B at a volume ratio of 1:1, add anhydrous magnesium sulfate, stir at 20-40°C for 12-24 hours, take the upper suspension, and rotary evaporate at 60-80°C for 4-6 hours to obtain a concentrated solution; add ether to the concentrated solution to precipitate a light yellow solid, and vacuum dry the light yellow solid at 60-80°C for 12-24 hours to obtain a monomer containing a dynamic covalent bond; The molar ratio of phenylboronic acid monomer to alcohol solvent is 1:(20-40); the molar ratio of 3-amino-1,2-propanediol to alcohol solvent is 1:(20-40); the molar ratio of anhydrous magnesium sulfate to phenylboronic acid monomer is (1-2):1; the molar ratio of ether to phenylboronic acid monomer is (20-30):1; Step S2. Add the monomer containing dynamic covalent bonds, the cross-linking agent having two or more functional groups, the monofunctional allyl linear monomer and the initiator obtained in step S1 into the electrolyte of the lithium-sulfur battery, and stir evenly to obtain a gel polymer electrolyte precursor; The monomer containing dynamic covalent bonds obtained in step S1 accounts for 1-5% of the total mass of the gel polymer precursor; The cross-linking agent with two or more functional groups accounts for 1-5% of the total mass of the gel polymer precursor; The monofunctional allyl linear monomer accounts for 1-5% of the total mass of the gel polymer precursor; The initiator accounts for 1-5% of the total mass of the gel polymer precursor; Step S3: The gel polymer precursor is thermally initiated to polymerize in situ to obtain a gel polymer electrolyte containing dynamic side chains.
2. The method for preparing a gel polymer electrolyte containing dynamic side chains according to claim 1, characterized in that: In step S1, the alcohol solvent is one of methanol, ethanol, and propanol, or a mixture of two or more thereof.
3. The method for preparing a gel polymer electrolyte containing dynamic side chains according to claim 1 or 2, characterized in that: In step S1, the phenylboronic acid-containing monomer is one or a mixture of two or more of 3-cyanophenylboric acid, 2-fluorophenylboric acid, 2,3,6-trifluorophenylboric acid, and 3,4,5,6-tetrafluorophenylboric acid.
4. The method for preparing a gel polymer electrolyte containing dynamic side chains according to claim 1 or 2, characterized in that: In step S2, the difunctional or higher cross-linking agent is one or a mixture of two or more of polydipentaerythritol hexaacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, and polyethylene glycol dimethacrylate.
5. The method for preparing a gel polymer electrolyte containing dynamic side chains according to claim 1 or 2, characterized in that: In step S2, the monofunctional allyl linear monomer is one or a mixture of two or more of 2-((allyloxy)methyl)ethylene oxide, 2-((2-(vinyloxy)ethoxy)methyl)ethylene oxide, and 2-(ethylene oxide)methacrylate.
6. The method for preparing a gel polymer electrolyte containing dynamic side chains according to claim 1 or 2, characterized in that: In step S2, the initiator is one or a mixture of two or more of azobisisoheptanonitrile, azobisisobutyronitrile, dibenzoyl peroxide, and methyl ethyl ketone peroxide.
7. The method for preparing a gel polymer electrolyte containing dynamic side chains according to claim 1 or 2, characterized in that: In step S2, the electrolyte of the lithium-sulfur battery is specifically: lithium bis(trifluoromethanesulfonyl imide) and LiNO3 are dissolved in 1,3-dioxolane and 1,2-ethylene glycol dimethyl ether to obtain the electrolyte of the lithium-sulfur battery; wherein the volume ratio of 1,3-dioxolane and 1,2-ethylene glycol dimethyl ether is 1:1, the concentration of lithium bis(trifluoromethanesulfonyl imide is 1M, and LiNO3 accounts for 2wt% of the total mass of the electrolyte.
8. The method for preparing a gel polymer electrolyte containing dynamic side chains according to claim 1 or 2, characterized in that: In step S3, the thermal initiation temperature is 50-80°C and the polymerization time is 1-4h.
9. The gel polymer electrolyte containing dynamic side chains prepared by the method for preparing a gel polymer electrolyte containing dynamic side chains according to any one of claims 1 to 8 is used in a lithium-sulfur battery.
Citation Information
Patent Citations
Boron-containing solid polymer electrolyte and preparation method and application thereof
CN106229547A
High-pressure-resistant gel-state polymer electrolyte as well as preparation method and application thereof
CN117638213A
In-situ preparation method of novel quasi-solid polymer electrolyte
CN117790877A
107 glue-based room-temperature end-capped silicone rubber and preparation method thereof
CN119708860A
Cross-linked polymer, ion conductive composition, gel state ion conductive composition and electrochemical element
JP2004059865A